DIGITAL MARKETING STRATEGY OF DRAGON FRUIT COMMODITY IN JAWAI DISTRICT, SAMBAS REGENCY - Windarti Windarti; Eva Dolorosa; Anita Suharyani (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
Dragon fruit is a plant that is widely cultivated and has a wide and diverse market reach so that it can improve the community's economy. Jawai District is an area that has the potential to cultivate dragon fruit with favorable climatic conditions. However, the increasing number of dragon fruit cultivation both within the region and outside the region will increase production so that an effective and efficient distribution channel is needed. The research objective is to understand the digital marketing of dragon fruit commodities. The research uses a qualitative descriptive method through data collection techniques with in-depth interviews about dragon fruit digital marketing strategies based on marketing mix indicators. The data analysis method used is SWOT analysis to identify internal and external elements and the AHP (Analytical Hierarchy Process) method to develop priority strategies. The results of the study using SWOT analysis show that the position is located at point (1.310; 0.086) or in quadrant 1, namely an aggressive strategy with an IFAS calculation of 2.586, and an EFAS calculation of 3.061. Determining strategic priorities using the AHP method produces alternative priority strategies, namely innovating with an attractive and up to date sales display, which results in a weight of 0.497. Conducting training and education related to digital marketing is the second priority which results in a weight of 0.242. These two strategies are a combination of choices to support the dragon fruit digital marketing strategy in increasing sales volume. Based on this, farmers need to innovate with attractive and up-to-date sales displays, such as adding digital platforms used by designing information so that promotional displays are more attractive. This should also be supported by training related to marketing from the Department of Agriculture.